The Implementation of Tanqih al-Manath Theory in Ushul al-Fiqh: An Analysis of Marriage Law Issues in Indonesia - Ismail Jalili Jalili; Fadillah Ulfa Ulfa; Abdul Kabir Hussain Solihu (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2024)
This study examines the application of Tanqih al-Manath theory in the context of marriage law in Indonesia, a country with a complex legal landscape influenced by both Islamic and secular laws. The aim of this study is to explore how Tanqih al-Manath theory can be effectively employed to resolve marriage law issues, providing a nuanced understanding of its implications in a modern legal setting. The state of the art reveals a gap in the comprehensive application of Tanqih al-Manath in current Indonesian marriage law, highlighting the need for a systematic analysis of its practical utility. Utilizing a qualitative research method, this study conducts an extensive review of relevant literature, legal texts, and case studies, alongside interviews with legal scholars and practitioners. The results indicate that Tanqih al-Manath theory offers a robust framework for addressing complex marriage law issues, such as polygamy, child marriage, and interfaith unions, by harmonizing traditional Islamic principles with contemporary legal demands. In conclusion, this study highlights the potential of Tanqih al-Manath theory to modernize marriage law in Indonesia by harmonizing classical jurisprudence with contemporary legal challenges. This approach can foster a more inclusive and relevant legal system, offering valuable insights for legal scholars and practitioners and paving the way for further exploration of Usul al-Fiqh theories.